Control of graft‐versus‐host disease with rabbit anti‐thymocyte globulin, rituximab, and bortezomib in TCRαβ/CD19‐depleted graft transplantation for leukemia in children: a single‐center retrospective analysis of two GVHD‐prophylaxis regimens. (3rd November 2019) - Shekhovtsova, Zhanna; Shelikhova, Larisa; Balashov, Dmitry; Zakharova, Viktoria; Ilushina, Maria; Voronin, Kirill; Kurnikova, Elena; Muzalevskii, Yakov; Kazachenok, Alexey; Pershin, Dmitry; Novichkova, Galina; Maschan, Alexey; et al.
Abstract: Both acute GVHD and chronic GVHD remain the leading cause of morbidity and death after allogeneic HSCT. We conducted a retrospective analysis comparing two GVHD‐prophylaxis regimens: 35 patients received "Regimen 1" (horse ATG, tacrolimus, and methotrexate) and 46 "Regimen 2" (rabbit ATG, rituximab, and peritransplant bortezomib). All 81 patients with a median age of 9 (0.6‐23) years with ALL (n = 31) or AML (n = 50) in complete remission received TCRαβ/CD19‐depleted transplants between May 2012 and October 2016, from 40 HLA‐matched unrelated and 41 haploidentical donors. After a median follow‐up of 3.9 years, the CI of acute GVHD II‐IV was 15% (95% CI: 7‐30) in the "Regimen 2" group and 34% (95% CI: −54) in the "Regimen 1" group, P = .05 . "Regimen 2" was also more effective in the prevention of chronic GVHD; the CI at 1 year after HSCT was 7% (95% CI: 2‐19) vs 31% (95% CI: 19‐51), P = .005 . The CI of relapse at 3 years adjusted for the GVHD‐prophylaxis regimen groups 31% (95% CI: 19‐51) for the "Regimen 1" vs 21% (95% CI: 11‐37) for the "Regimen 2", P = .3. The retrospective observation suggests that the use of the rATG, rituximab, and bortezomib was associated with significantly lower rate of GVHD without the loss of anti‐leukemic activity.